2000
DOI: 10.1016/s0896-6273(00)00064-7
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Dependent Regulation of Neurotransmitter Release at Central Synapses

Abstract: Depolymerization of actin by latrunculin A transiently promotes neurotransmitter release. The mean rate of mEPSCs increases by a Ca2+-independent process, without a concomitant change in the mean amplitude. The readily releasable vesicle pool size and the rate of refilling of the readily releasable pool remain unaltered by latrunculin treatment. Evoked neurotransmitter release also increases in a manner consistent with an increase in vesicle release probability. The observed enhancement of neurotransmitter rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
259
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(283 citation statements)
references
References 45 publications
24
259
0
Order By: Relevance
“…These values are not different from those of control experiments, which suggests that latrunculin has no augmenting effects on quantal release probability. Such an effect had been described in hippocampal cultures (Morales et al, 2001). On the other hand, during second pulses, EPSCs were much smaller; this can be seen by comparing Figures 1 A and 4 A (arrows).…”
Section: Nem and Staurosporine Do Not Affect Recruitment Of Releasablmentioning
confidence: 67%
“…These values are not different from those of control experiments, which suggests that latrunculin has no augmenting effects on quantal release probability. Such an effect had been described in hippocampal cultures (Morales et al, 2001). On the other hand, during second pulses, EPSCs were much smaller; this can be seen by comparing Figures 1 A and 4 A (arrows).…”
Section: Nem and Staurosporine Do Not Affect Recruitment Of Releasablmentioning
confidence: 67%
“…Several studies have shown that synaptic vesicles are associated with a variety of cytoskeletal and motor proteins (Dresbach et al 2001;Evans et al 1998;Miyamoto 1995;Morales et al 2000;Prekeris and Terrian 1997;Ryan 1999). The synapsin family of phosphoproteins, which tethers vesicles to actin filaments, has been studied the most (Benfenati et al 1989;Greengard et al 1993;Pieribone et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic studies and the subsynaptic distribution of actin filaments also suggest a role for actin in neurotransmitter release (13,14). Actin depolymerizing proteins of the actin depolymerizing factor (ADF)/cofilin family are essential regulators of actin dynamics (15).…”
mentioning
confidence: 99%